2010
DOI: 10.1364/oe.18.016387
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive phase-shift lithography photomask operating in proximity printing mode

Abstract: A phase shift proximity printing lithographic mask is designed, manufactured and tested. Its design is based on a Fresnel computergenerated hologram, employing the scalar diffraction theory. The obtained amplitude and phase distributions were mapped into discrete levels. In addition, a coding scheme using sub-cells structure was employed in order to increase the number of discrete levels, thus increasing the degree of freedom in the resulting mask. The mask is fabricated on a fused silica substrate and an amor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Two years later, Neto et al [182] and in 2009 Cirino et al [183,184] both demonstrated 1.5 lm resolution with a very similar configuration. Recently, Weichelt et al have demonstrated that a phase mask with only two phase levels and an additional chromium layer is sufficient to realize a resolution of 2 lm for a non-periodic pattern in 30 lm separation [87].…”
Section: Trendsmentioning
confidence: 86%
“…Two years later, Neto et al [182] and in 2009 Cirino et al [183,184] both demonstrated 1.5 lm resolution with a very similar configuration. Recently, Weichelt et al have demonstrated that a phase mask with only two phase levels and an additional chromium layer is sufficient to realize a resolution of 2 lm for a non-periodic pattern in 30 lm separation [87].…”
Section: Trendsmentioning
confidence: 86%
“…The Talbot effect allows to directly image the shape of the angular spectrum onto the wafer, 6 while phase shift masks can be used in conjunction with a coherent illumination to print extremely small structures using the principles of holograpy. 7 Although these techniques have a great potential for special applications, we will focus on a more general approach in the following.…”
Section: The Role Of the Illumination In Proximity Printingmentioning
confidence: 99%
“…Schematic diagram of the phenomenon of free space propagation, and its relation with frequency and image spaces, as well as mask and wafer planes. Reprinted with permission of OSA (Cirino, G. A., 2010).…”
Section: Complex-amplitude Modulation Cgh: Diffractive Lithography Phmentioning
confidence: 99%
“…A(x',y') and (c) phase φ(x',y') distributions of the resulting phase shift photomask. Reprinted with permission of OSA (Cirino, G. A., 2010). Figure 11 shows schematically the entire process to fabricate the proposed diffractive phase shift proximity photomask.…”
Section: A(x'y') [0mentioning
confidence: 99%